Reversible Inhibitors of LSD1 as Therapeutic Agents in Acute Myeloid Leukemia: Clinical Significance and Progress to Date. Issue 3 (24th November 2014) - Mould, Daniel P.; McGonagle, Alison E.; Wiseman, Daniel H.; Williams, Emma L.; Jordan, Allan M.
Abstract In the 10 years since the discovery of lysine‐specific demethylase 1 (LSD1), this epigenetic eraser has emerged as an important target of interest in oncology. More specifically, research has demonstrated that it plays an essential role in the self‐renewal of leukemic stem cells in acute myeloid leukemia (AML). This review will cover clinical aspects of AML, the role of epigenetics in the disease, and discuss the research that led to the first irreversible inhibitors of LSD1 entering clinical trials for the treatment of AML in 2014. We also review recent achievements and progress in the development of potent and selective reversible inhibitors of LSD1. These compounds differ in their mode of action from tranylcypromine derivatives and could facilitate novel biochemical studies to probe the pathways mediated by LSD1. In this review, we will critically evaluate the strengths and weaknesses of published series of reversible LSD1 inhibitors. Overall, while the development of reversible inhibitors to date has been less fruitful than that of irreversible inhibitors, there is still the possibility for their use to facilitate further research into the roles and functions of LSD1 and to expand the therapeutic applications of LSD1 inhibitors in the clinic.